Influence of root canal sealer composition on postoperative pain after endodontic treatment of permanent teeth: a systematic review and meta-analyses - Moraes, Vania Gomes; Meyfarth, Sandra Regina Santos; Maranón-Vásquez, Guido Artemio; Antunes, Lívia Azeredo Alves; Antunes, Leonardo Santos (Brazilian Dental Science, 2024)
Postoperative pain is a frequent complication after root canal treatment. Its management is an important aspect of endodontic practice. Some treatment-related parameters were associated with the development of postoperative pain, including the sealer composition and extrusion. Objective: This systematic review aimed to answer the clinical question: Do root canal sealers composition influence postoperative pain after endodontic treatment of permanent teeth? Material and Methods: Electronic searches were conducted in PubMed, Scopus, Web of Science, Cochrane, LILACS, and grey literature databases until September 2021. The studies were qualitatively assessed using the RoB2 tool (Cochrane) and the certainty of evidence (GRADE). Sensitivity and pooled estimates were calculated using a random-effects model. Twelve articles were included. Results: The risk of bias was high in one study, low in nine, and two had some concerns. Qualitative analyses showed no influence of sealer extrusion on postoperative pain. Meta-analyses showed no significant difference in postoperative pain with moderate to very low levels of certainty between AH Plus and calcium silicate-based sealers, in a 95% confidence interval. Analysis between AH Plus, Zinc Oxide and Eugenol (ZOE), and calcium hydroxide (Ca(OH)2)-based sealers were not performed due to heterogeneity and lack of data. Conclusion: Literature showed contrasting results in postoperative pain between AH Plus and ZOE-based sealers, with low to moderate certainty of evidence. Regarding Ca(OH)2-based sealers, a single study with a low level of certainty concluded that AH Plus presented less postoperative pain than Apexit Plus. Therefore, further studies are needed to assess the influence of these sealers on postoperative pain. Evidence showed no difference in postoperative pain between AH Plus and calcium silicate-based sealers. Sealer extrusion is a variable that requires further studies. KEYWORDS Postoperative pain; Root canal treatment; Sealer composition; Sealer extrusion; Systematic review.